Competitive barriers in a acquiring business internationally: A case on Malaysian firms - Mohtar, Shamimi; Hussain, Fawad (2010)
In trend with the current economic situation that has affected the international industry world wide, this paper previews literature, which focuses on internationalization strategy, internet communication, ecommerce and Malaysian firm which involve in the process of internationalization. Over the past few decades the internationalization has change the concept and ideology how the international market was perceived. The aim of this paper is to examine internationalization strategies among the Malaysian firms and competitive advantage of internationalization for Malaysian firms. This paper will look into, what are the approaches needed to innovate the environment for firm to go via internationalization process. The Malaysian local firms can only survive, when they have competitive advantage over products and services. These competitive advantages can depend on managerial approach, strategy and perception of the international markets (Javalgi, R. R. G., et al, 2003). It is important to reduce the trade barriers for Malaysian firms. These approaches will also support Malaysian local firms and provide better opportunities for Malaysian local firms to grow internationally with a competitive edge.